Proximal Hamstring Injuries: Review of Operative and Nonoperative Management - Buckwalter V, Joseph; Duchman, Kyle; Amendola, Ned (The Journal of Hip Surgery, 2018)
While uncommon, proximal hamstring injuries can result in significant pain and dysfunction, while also posing considerable treatment dilemmas due to the spectrum of injury that exists. Recent literature suggests that outcomes are improved with acute surgical repair of complete proximal hamstring avulsions, highlighting the importance of timely management of these unique injuries. While chronic repair or reconstruction can result in predictable improvements in pain and function postoperatively, the results are less predictable than acute surgical repair. Nonoperative management should be considered as the initial treatment strategy for patients with proximal hamstring tendinopathy or partial tears, as delayed surgical intervention in this setting has not been shown to significantly affect outcomes. Although current evidence is limited, evolving therapeutic techniques, including biologic injections and endoscopic repair techniques, need to be carefully evaluated to determine their role moving forward. This review aims to provide updated information on the relevant anatomy, mechanism of injury, diagnosis, and management of proximal hamstring injuries, with a specific focus on surgical indications, techniques, and outcomes.
Keywords: proximal hamstring injury; proximal hamstring tear; proximal hamstring avulsion; proximal hamstring tendinopathy; hamstring repair